2004
DOI: 10.1128/jvi.78.9.4776-4782.2004
|View full text |Cite
|
Sign up to set email alerts
|

Scrapie Protein Degradation by Cysteine Proteases in CD11c + Dendritic Cells and GT1-1 Neuronal Cells

Abstract: Dendritic cells (DC) of the CD11c؉ myeloid phenotype have been implicated in the spread of scrapie in the host. Previously, we have shown that CD11c؉ DC can cause a rapid degradation of proteinase K-resistant prion proteins (PrP Sc ) in vitro, indicating a possible role of these cells in the clearance of PrP Sc . To determine the mechanisms of PrP Sc degradation, CD11c ؉ DC that had been exposed to PrP Sc derived from a neuronal cell line (GT1-1) infected with scrapie (ScGT1-1) were treated with a battery of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 61 publications
2
29
0
Order By: Relevance
“…SD: 10,641.04 (free medium) and 10,786.49 (PrP Sc -loaded medium). The experiment was repeated four times (Luhr et al 2002(Luhr et al , 2004 our model used peripheral primary neurons that were infected in vivo after oral scrapie challenge (Beekes and McBride 2007). Thus our model speciWcally targeted a cell-to-cell transmission of PrP Sc (Caughey and Baron 2006) from the immune system to the PNS, hypothetically at the genesis of the prion peripheral neuroinvasion (Kimberlin and Walker 1989).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SD: 10,641.04 (free medium) and 10,786.49 (PrP Sc -loaded medium). The experiment was repeated four times (Luhr et al 2002(Luhr et al , 2004 our model used peripheral primary neurons that were infected in vivo after oral scrapie challenge (Beekes and McBride 2007). Thus our model speciWcally targeted a cell-to-cell transmission of PrP Sc (Caughey and Baron 2006) from the immune system to the PNS, hypothetically at the genesis of the prion peripheral neuroinvasion (Kimberlin and Walker 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The role of DCs in prion disease appears to be ambiguous. Some authors have shown, through in vitro models, that DCs can impair prion dissemination and that they are able to process PrP Sc , by cysteine protease, and to decrease the amount of infectivity associated with scrapie (Luhr et al 2002(Luhr et al , 2004 or BSE (Rybner-Barnier et al 2006). Several studies have demonstrated that DCs act in the spreading of prions.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, when formation of PrP Sc was blocked by PPS (Caughey and Raymond, 1993) during the BDNF treatment, no effect on PrP Sc levels was seen, which makes it unlikely that the BDNF effect is attributable to a decrease in PrP Sc degradation. In contrast, when degradation of PrP Sc was inhibited with leupeptin (Luhr et al, 2004a), BDNF caused an increase in PrP…”
Section: Discussionmentioning
confidence: 88%
“…The results of ARNOLD et al (1995) and SUPATTAPONE et al (1999SUPATTAPONE et al ( , 2001 give evidence for a potential involvement of the endosomal cysteine protease cathepsin B (CTSB) in degradation of the abnormal prion protein isoform (PrP Sc ), which is underlined by the investigations of LUHR et al (2004aLUHR et al ( , 2004b who found out that degradation of PrP Sc in scrapie infected neurons is carried out by cysteine proteases at a sour pH and that addition of a selective CTSB inhibitor leads to a significant increase of the PrP Sc content. Concerning the lysosomal aspartate protease cathepsin D (CTSD), several expression studies reported an elevated concentration of the respective enzyme within the course of scrapie infection in mice (BROWN et al 2004, RIEMER et al 2004, XIANG et al 2004.…”
Section: Introductionmentioning
confidence: 85%